Scarless Neck Feminization: Chondrolaryngoplasty Through Endoscopic Transoral Vestibular Approach. (15th September 2022) - Banuchi, Victoria E.; Helman, Samuel N.
Abstract : We present in this paper a novel approach to perform endoscopic chondrolaryngoplasty without any external visible scars. The technique involves utilizing the endoscopic transoral vestibular approach. We have modified the technique by using the placement of a suture immediately above the anterior commissure, which provides a marker for the inferior extent of cartilage resection. Laryngoscope, 133:1099–1102, 2023